Keeping it together: How to design legal protection against multiple and intersectional discrimination - Côrte-Real, P.; Rego, M. L.; Brilhante, J.; Resende, M. J.; Vale de Almeida, M.; Corcodel, V. (International Journal of Discrimination and the Law, 2025)
This paper presents the development of a cohesive set of scientifically grounded recommendations aimed at harmonizing anti-discrimination protections. These recommendations, rooted in multidisciplinary knowledge, address the complexities of sequential, additive, and intersectional multiple discrimination. Through a multidisciplinary approach that combines Law, Social Anthropology, and Economics, this work uses qualitative data to formulate empirically grounded proposals. One of the key recommendations is the adoption of a single law and the establishment of a single entity—the Equality Agency—to eliminate the fragmentation and other institutional challenges identified during fieldwork. By integrating social and legal analysis, the paper proposes a redesign of legal and institutional frameworks to better protect against various forms of discrimination. It acknowledges the structural nature of discrimination and recognizes the need for an integrated response to the complexities of the experiences of those affected. While Portugal serves as the primary context for this research, we believe that the principles, methodologies, and overarching logic of this approach have broader applicability, offering valuable insights for addressing multiple and intersectional discrimination in other contexts.